(untitled) (Research Nepal Journal of Development Studies, 2018)
There is constitutional provision to include the marginalized community i.e. Dalit in every step of development and structure of development but there are negligible representatives from Dalit community those are also targeted from elite Dalit. Inherited caste identity is an important determinant of life opportunities for Dalit communities where they have the historical skill and knowledge that could be advanced for the prosperity. This study asks why addressing development-based inequality and discrimination does not feature in inter-governmental commitments such as the sustainable development goals which clearly focuses on no one left behind in the development process. In order to trace out the political inequality of Dalit and to generalize the findings, both primary and secondary qualitative data have been interpreted and analyzed. The key informant interview method was employed to explore the experiences of Dalit on the current province government political inequality, identity debates, and representation. Furthermore, the review emphasizes the base of inequality in political representative and development process is the mindset of the political leader and more focus on the number of votes rather than the true implementation of the constitutional provision for inclusion. The history of Dalit culture and their deplorable situation in Karnali are suffering from the caste-based discrimination in the name of untouchability.